2019
DOI: 10.3390/s19143164
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Diffusion Based Multiplicative Speckle Noise Removal

Abstract: Multiplicative speckle noise removal is a challenging task in image processing. Motivated by the performance of anisotropic diffusion in additive noise removal and the structure of the standard deviation of a compressed speckle noisy image, we address this problem with anisotropic diffusion theories. Firstly, an anisotropic diffusion model based on image statistics, including information on the gradient of the image, gray levels, and noise standard deviation of the image, is proposed. Although the proposed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…During the testing phase, speckle-affected test images were used to assess filtering performance. Anisotropic diffusion filtering can preserve and enhance edge information while subduing any noise [ 24 , 47 ]. The gradient operator detects the edge information along with noise [ 48 ].…”
Section: Proposed Methodologymentioning
confidence: 99%
“…During the testing phase, speckle-affected test images were used to assess filtering performance. Anisotropic diffusion filtering can preserve and enhance edge information while subduing any noise [ 24 , 47 ]. The gradient operator detects the edge information along with noise [ 48 ].…”
Section: Proposed Methodologymentioning
confidence: 99%
“…The problem of edge blurring is mildly resolved in ADMSS [41] by extending the formulation of Cottet and Ayyadi [42] to perform selective diffusion so that diffusion across the fine structures and homogeneous regions are discriminated and in this way visibility of important structures is enhanced. Fick's law based physical diffusion equation theory is used in doubly degenerate nonlinear diffusion (DDND) model by Zhou et al [43] to promote de-noising process as given below: 𝜎 𝑠𝑝𝑒𝑐𝑘𝑙𝑒 = 2,3,4 IDDND [47] 𝜎 𝑠𝑝𝑒𝑐𝑘𝑙𝑒 = 2,3,4 GAD-LBM [48] 𝑉 𝑠𝑝𝑒𝑐𝑘𝑙𝑒 = 0.03,0.12 SGS-SRAD [49] ∆ 𝑡 = 𝑉 𝑠𝑝𝑒𝑐𝑘𝑙𝑒 = 0.03,0.120.1, 𝑛 𝑖𝑡𝑒𝑟 = 100 Frost [29] Kuan [30] Gamma [31] • Successfully inhibit smoothing near edges.…”
Section: Speckle Noise Reductionmentioning
confidence: 99%
“…where 𝛽(𝐼) = {1 − 𝑏(𝐼)} is a region indicator function. Gao et al [47] observed erroneous pixels appear in homogeneous background of the image obtained by ADMSS [41] and therefore they developed an improved DDND model (IDDND) for multiplicative speckle reduction. Xu et al [48] suggested Gabor filter based anisotropic diffusion (GAD-LBM), supporting the advantages of the Lattice Boltzmann method [81] on rapid parallel implementation.…”
Section: Sgs-srad [49]mentioning
confidence: 99%
See 1 more Smart Citation
“…The performance is evaluated in terms of PSNR and SSIM with respect to standard data. Gao et al 36 have structured anisotropic diffusion-based filter for the removal of multiplicative speckle noise. To structure the anisotropic diffusion its divergence term is decompose that helps to recognize the edges and boundary effectively.…”
Section: Introductionmentioning
confidence: 99%